Clinical Study To Evaluate The Efficacy Of Triphaladi Ghrita Yonipichu In Paripluta Yonivyapat With Special Reference To Pelvic Inflammatory Disease. - Mathapati, Shweta P; Rawal, P K; Shiraguppi, Sunita (International Research Journal of Ayurveda & Yoga, 2021)
Pelvic inflammatory disease is a major problem to the health of young maiden. PID may be asymptomatic or subclinical. The incidence varies from 1-2% per year among sexually active women. About 85% are spontaneous infection in sexually active females of reproductive age. The 15% follow procedures, which favors the organism to ascend up. PID affects one woman in 10 during her reproductive year 25% will have serious sequels including infertility, pelvic pain, ectopic pregnancy, Hysterectomy, Oophorectomy. In our classics Paripluta is one among yonivyapat explained with dominancy of Pitta- Vata predominance as mentioned in Bhavaprakash in Yonirogadhikar, so mentioned above herbal preparation has been trial here.